72.0k views
2 votes
Can any kind soul help me please​

Can any kind soul help me please​-example-1
User Galdor
by
5.5k points

1 Answer

5 votes

Answer:

p-q= -4

p=q-4

x^2 + px + q=0

=> x^2 + (q-4)x + q = 0

d= b^2-4ac

=(q-4)^2 - 4(1)(q)

= q^2 + 16 -8q - 4q

=q^2 -12q+16

given that D=16

q^2 -12q+16 = 16

=> q^2 -12q = 0

=> q^2 = 12q

=> q = 12q/q

=> q= 12

Therefore the value of q is 12 and the value of p is q-4 = 12-4= 8

Hope you understood............

User Artem Govorov
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.